Attachment of an oligopeptide epitope to the C-terminus of recombinant SIV gp160 facilitates the construction of SMAA complexes while preserving CD4 binding. - Hanke, T; Young, D; Doyle, C; Jones, I; Randall, R (1995)
A small 14 amino acid oligopeptide tag (termed SV5-Pk) was fused onto the carboxy-terminus of simian immunodeficiency virus gp160 expressed from a recombinant baculovirus. The presence of the Pk tag had no obvious effect on the expression and glycosylation of gp160 and did not interfere either with CD4 binding or with cleavage at its maturation site by the protease furin. The presence of the Pk tag did, however, facilitate the simplified purification of full-length gp160 and its incorporation into immunogenic solid matrix-antibody-antigen (SMAA) complexes.